Uma Nova Fase Polimórfica do Cristal de NaGd(MoO4)2: Síntese Hidrotérmica, Estrutura e Transição de Fase Induzida por Temperatura - DORNELES, Maria Luiza de Araujo (2024)
Sodium gadolinium molybdate, NaGd(MoO4)2, is a versatile material with intriguing physical properties and potential industrial applications. Previous literature reports that this material crystallizes in the scheelite-type tetragonal structure (space group I41/a). This study presents the synthesis and characterization of NaGd(MoO4)2 microcrystals, which crystallize in a metastable fergusonite-type structure (space group I2/a). Temperature-dependent X-ray diffraction (XRD) and Raman spectroscopy measurements confirmed the high purity and crystallinity of the synthesized microcrystals. In situ temperature-dependent XRD and Raman spectroscopy were conducted to elucidate the structural properties and stability of this novel phase. Comprehensive and unprecedented characterization of the material's structural properties under extreme temperature conditions revealed an irreversible thermally induced phase transition from the monoclinic to a more stable scheelite-type tetragonal phase (space group I41/a) at approximately 813 K. The Raman spectra of the monoclinic system provided additional evidence for the occurrence of the fergusonite-scheelite structural transition. This study deepens the understanding of phase transitions in molybdate compounds and suggests the potential application of these materials in various temperature- dependent industrial sectors, particularly in lasers, materials with high luminescence, and scintillation.